Classic cases in medical ethics : - Pence, Gregory E (McGraw-Hill, 2004)
Offers a collection of major cases defining and shaping the field of medical ethics. Includes new material on research in embryo research, stem cells, and reproductive cloning. Also discusses paid organ donation, international bioethics, and costs of prescription drugs for the elderly